City chickens - Heppermann, Christine (Houghton Mifflin Books for Children, 2012)
Just outside of downtown Minneapolis, follow the sounds of crowing and clucking and you will find Mary Britton Clouse's Chicken Run Rescue. Over the years, Mary and her husband have given hundreds of homeless birds a safe place to rest until they can be adopted by caring families.